Imparting flame resistance to citric acid–modified cotton fabrics using DNA. (June 2020) - Luo, Qiulan; Gao, Pu; Zhou, Jie; Zhang, Jian; Wu, Wen; Cao, Jianda; Reddy, Narendra; Ma, Hui
Textiles are one of the basic needs of humankind. Although textiles satisfy many human needs, they are implicated in the loss of life and property since many fibers and fabrics are inflammable. Many chemical finishes are applied to improve the flame resistance of textile materials. Unfortunately, most of the flame retardants are synthesized chemically, need large quantities to be used, cause adverse impact on the textiles and also expensive. In this research, a novel approach to using DNA from herring sperm as flame retardant for cotton was explored. Surface of the textiles was modified with citric acid to increase free carboxyl content and hence absorption of DNA. It was observed that DNA was absorbed into the cotton fabrics using chemical adsorption according to the quasi-second-order-kinetic model. Flammability of the cotton before and after the addition of DNA was checked. It was observed the length of fabrics damaged due to flames was only 29 mm compared to the original length of 350 mm. Such a high increase in flame resistance has not been reported for natural materials. In addition, the chemical reaction between DNA and cotton fabric can improve the flame retardant–washing resistance of the finished cotton fabric. In this article, the strategy of using biological macromolecules to flame-retardant fabrics can provide research basis for the design and development of efficient and environmentally friendly flame retardants.